Promovendo a sustentabilidade: o impacto das práticas ESG na redução das emissões de carbono nas indústrias brasileiras - Santos, Otavio Augusto Silva dos (Universidade Federal de São Carlos, 2024)
The study addresses the relationship between environmental, social, and corporate governance (ESG) practices and carbon emission reduction in Brazilian industries. The introduction highlights the growing global importance of sustainability and the adoption of ESG metrics as a central strategy for responsible companies. In the Brazilian context, the coexistence of economic development and environmental sustainability is crucial, especially given the country's significant contribution to carbon emissions. The study conducts a literature review using the Scopus database and the CAFe system from the CAPES Periodicals Portal to search for relevant articles. Keyword selection includes terms related to ESG and carbon emissions, with specific filters to ensure document relevance to the Brazilian context. A bibliometric analysis is conducted using VOSviewer, exploring the co-occurrence of keywords in 31 selected articles. Visualization highlights five main clusters, addressing topics from sustainable development to specific issues such as corporate social responsibility and sustainable finance. Temporal analysis reveals an exponential increase in scientific publications on ESG from 2016 to 2024. Document analysis focuses on four articles measuring carbon emissions in different contexts, including assessments of ports, financial efficiency, and environmental performance in energy companies. Results show a variety of environmental metrics used, highlighting diversity in measurement approaches. The conclusion emphasizes the growing interest in ESG practices but highlights the lack of a standardized methodology for measurement, presenting this as a central challenge. The study suggests the need to further explore social and governance dimensions for a comprehensive understanding of the ESG landscape in Brazilian industries. Despite not obtaining a large number of results in the specific search for CO2 emission reduction, the work underscores the continued importance of sustainable approaches for the country's economic and environmental development.
Promoting sustainability: the impact of ESG practices on reducing emissions carbon in brazilian industries
Keywords: Sustentabilidade; Métricas ambientais; Responsabilidade ambiental; Sustainability; Environmental metrics; Environmental responsibility; OUTROS::CIENCIAS